(untitled) (Nigerian Journal of Technology, 2019)
The knowledge of Fracture Pressure Gradient (FPG) from Pore pressure and Overburden pressure prediction is one of the requirements to safe drilling. This provides sufficient information to drilling engineers on the appropriate drilling mud weight, casing design criteria, and optimum penetration rates. Several models were evaluated for formation fracture pressure gradient (FPG) prediction and were found to be inaccurate for the Niger Delta environment. A modified Eaton model has been developed for the Niger Delta environment that considers the variation of the Poisson’s ratio (v) with depth. It was also established from the sensitivity analysis carried out that the density input parameter is critical in the development of the modified model. The results showed that the formations will tend to fracture at depths of about 6700ft-10000ft in the Niger Delta area at Poisson’s ratio of about 0.35-0.40. In the light of the foregoing, the modified model was found to be most accurate for predicting formation fracture pressure gradient (FPG) particularly for the Niger Delta environment. http://dx.doi.org/10.4314/njt.v38i3.13